Effectiveness of Interdisciplinary Approach in Midwifery Higher Education Curriculum : Scoping Review - Fernandez, Veronica; Susanti, Ari Indra (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to analyze the effectiveness of the interdisciplinary approach in midwifery higher education curricula. The research method utilized a scoping review of the Scopus, PubMed, and ScienceDirect databases. This method included the identification of research questions, searching for appropriate literature, selecting relevant studies, and mapping and analyzing data to identify knowledge gaps. The data analysis technique employed was thematic analysis. The results identified ten key articles that highlighted several key themes: midwifery education and training models, implementation of global standards, innovation in learning, and interprofessional collaboration. Findings showed that the Continuity of Midwifery (CoM) approach and mentor training positively impacted students' learning experiences, but clinical evaluation and supporting facilities still require significant improvement. The CoM education model underscored students' preferences for autonomous and collaborative practice. Enhancements to clinical evaluation and support facilities were recognized as important steps to improve the quality of education. Additionally, the implementation of global standards and innovation in interprofessional education is crucial for improving interprofessional collaboration and care outcomes. It is recommended to strengthen interprofessional approaches and community learning, as well as to engage students as researchers, to prepare them for the complex challenges in midwifery practice. These steps are expected to enhance the competency of midwifery graduates globally.